Strategy Implementation During A Recession : A Case Study Of Honda Corporation - Shuaibu, Umar (2009)
This case study is aimed at magnifying the recession strategies og Honda Corporation in relation to other companies with view of understanding the causes of its success or otherwise in dealing with the recession.